2009
DOI: 10.1016/j.trstmh.2009.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Differences in clinical and laboratory characteristics and disease severity between children and adults with dengue virus infection in Taiwan, 2002

Abstract: To compare the clinical and laboratory characteristics and disease severity between adults and children with dengue in Taiwan in 2002, we retrospectively studied 661 serologically confirmed dengue-infected patients (606 adults and 55 children) admitted between June and December 2002 to a single medical centre. The medical charts of the patients were reviewed for demographic, clinical, laboratory and imaging information. Compared with children, adult patients were found to have: higher incidences of arthralgia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 23 publications
7
51
0
2
Order By: Relevance
“…Out of 26 positive cases, 12 were males and 14 were females. This data is consistent with the previous reports suggesting no difference, a male excess, or a female excess in dengue patient populations [36][37][38][39][40]. Bhaskar et al [30] also found no difference in male to female ratio in an observational study in Chennai, south India [41].…”
Section: Discussionsupporting
confidence: 92%
“…Out of 26 positive cases, 12 were males and 14 were females. This data is consistent with the previous reports suggesting no difference, a male excess, or a female excess in dengue patient populations [36][37][38][39][40]. Bhaskar et al [30] also found no difference in male to female ratio in an observational study in Chennai, south India [41].…”
Section: Discussionsupporting
confidence: 92%
“…Además del compromiso hepático, se ha descrito el de los sistemas nervioso central y cardiovascular (33,34), sin embargo, en ningún paciente de este estudio se registraron estas complicaciones, lo cual coincide con lo reportado en otras series en ancianos (19,21,35).…”
Section: Discussionunclassified
“…26 Another study showed numerous acute clinical findings more often in Vietnamese adults than children, including arthralgia, myalgia, upper gastrointestional bleeding, abdominal pain, thrombocytopenia, and elevated transaminases. 27 Finally, a study from Singapore that evaluated non-acute symptoms such as fatigue 2 months after first detection of DENV infection found a greater proportion in older subjects as compared with younger subjects.…”
Section: Discussionmentioning
confidence: 99%